SYARAT CUKUP UNTUK OPTIMALITAS MASALAH KONTROL KUADRATIK LINIER - Suci Fratama Sari (Jurnal Matematika UNAND, 2013)
The LQR problem is an optimal control problem which is now used in variouselds of science. The optimal control is given by u(t) = ????Kx(t), where K = R????1(PB)Tand P is a unique positive semidenite solution of Algebraic Riccati Equation (ARE).The existence of optimal control u(t) depends on the existence matrix P. In this paper,the sucient conditions which ensures the existence and uniqueness of the optimal con-trol u(t) will be determined. Moreover, some examples as an illustration of the LQRproblem will be given.